Oras na para lumaban (Regal Entertainment., 2000)
Gary Estrada plays a lowly youth who grows-up an illegitimate child and who later gets disowned by his father, a much idolized public official and crusader. When rotten elements in the law enforcement trump up charges against Gary, he becomes fugitive who goes up against great odds to clear his name.